Demokrasi Sebagai Pola Hidup Menurut John Dewey - C.B Mulyatno (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2011)
Abstract: John Dewey expresses repeatedly that the significance of democracy is more than political discourse. He invites us to realize that democracy is primarily moral idea that animates a process of living and should be actualized continuously. He underlines that the idea of liberty, equality and fraternity, which is the democratic trinity, is ethical ideal of humanity in which personality is at the centre of reflection. Every human individual is free to actualize its self-realization. His liberty is based on the belief that every human individual has a right to equal opportunity with every other person to develop whatever endowment he has. Then, democracy indicates fraternity as an ethical value, which every human individual is able to actualize his capacities only in actively cooperative relationship with other. Political and social democracy presenting in a real association of life will be effectively sustained if its values of ideal hu-manity becomes an animating force of life. In other words, he envisions that democracy becomes a personal way of life. Keywords: values of democracy, social responsibility, culture of democracy, transformation of life, peaceful life. Absrak: John Dewey menyatakan berulangkali bahwa demokrasi lebih dari sekedar persoalan politik. Ia menunjukkan bahwa demokrasi pertama-tama merupakan sebuah gagasan etis yang menjiwai proses hidup secara terus-menerus. Kebebasan, kesederajatan, dan persaudaraan yang menjadi inti demokrasi merupakan nilai-nilai etis kemanusiaan yang menjadi arah hidup manusia di dalam kehidupan bersama di tengah masyarakat. Setiap individu adalah bebas untuk mewujudkan dirinya. Kebebasannya didasarkan pada keyakinan bahwa setiap individu mempunyai hak dan kesempatan yang sama untuk mengembangkan diri sesuai dengan potensi yang dianugerahkan kepadanya. Persaudaraan merupakan nilai etis yang menegaskan bahwa setiap individu hanya mampu mewujudkan diri di dalam relasi dan kerjasama dengan sesamanya. Ketiga nilai etis tersebut seharusnya menjiwai tata hidup bersama. Dengan kata lain, demokrasi seharusnya menjadi pola hidup setiap pribadi sebagai anggota masyarakat. Kata-kata Kunci: nilai-nilai demokrasi, tanggung jawab sosial, budaya demo-krasi, transformasi hidup, hidup damai.